2018
DOI: 10.1002/wcc.565
|View full text |Cite
|
Sign up to set email alerts
|

Explaining differential vulnerability to climate change: A social science review

Abstract: The varied effects of recent extreme weather events around the world exemplify the uneven impacts of climate change on populations, even within relatively small geographic regions. Differential human vulnerability to environmental hazards results from a range of social, economic, historical, and political factors, all of which operate at multiple scales. While adaptation to climate change has been the dominant focus of policy and research agendas, it is essential to ask as well why some communities and peoples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
333
1
20

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 503 publications
(358 citation statements)
references
References 147 publications
(172 reference statements)
4
333
1
20
Order By: Relevance
“…With the more contemporary approaches, vulnerability is not only “a characteristic or state generated by multiple environmental and social processes” and “exacerbated by climate change” but also reflective of the “capacity of individuals and social groups to respond to […], cope with, recover from or adapt to, any external stress placed on their livelihoods and well‐being” (Kelly & Adger, 2000, p. 325). It is, therefore, a “multidimensional process affected by social, political, and economic forces interacting from local to international scales” (Thomas et al, 2018, p. 2).…”
Section: Theoretical Framework and Key Conceptsmentioning
confidence: 99%
“…With the more contemporary approaches, vulnerability is not only “a characteristic or state generated by multiple environmental and social processes” and “exacerbated by climate change” but also reflective of the “capacity of individuals and social groups to respond to […], cope with, recover from or adapt to, any external stress placed on their livelihoods and well‐being” (Kelly & Adger, 2000, p. 325). It is, therefore, a “multidimensional process affected by social, political, and economic forces interacting from local to international scales” (Thomas et al, 2018, p. 2).…”
Section: Theoretical Framework and Key Conceptsmentioning
confidence: 99%
“…According to Mostert, the allocation of responsibility should include such principles as minimizing social costs, acknowledging existing capacities and building on solidarity. As a next step in this field, this would imply connecting the responsibility of adaptation discussion to the one on adaptive capacity (Siders, ) and differential vulnerability (Thomas et al, ), and the impacts of adaptation on vulnerability (Atteridge & Remling, ). This would enable us to see how responsibilities may be reallocated under different principles.…”
Section: Resultsmentioning
confidence: 99%
“…While no past society is a direct model of present societies, past societies provided similar arrays of services to their members, such as economic and trade relationships, food and shelter, belief systems, governance structures, social norms, and cultural traditions. At the same time, there is evidence that the forms of past societies also have influenced, to varying degrees, institutions and settlement patterns that exist today (17)(18)(19)(20).…”
Section: Archaeology Of Sustainability and Changementioning
confidence: 99%
“…From 2016 to 2018, the USGCRP Social Science Coordinating Committee (SSCC) (of which both co-authors were members) led the most recent effort to address these concerns. This included a workshop (47) that brought together social science professional societies with federal social scientists and produced a series of three white papers (10,20,(48)(49)(50). As one of these papers outlined tools of social science, including definitions of what archaeology is and how it does its work (10), this project indicated that awareness and understanding of archaeology and other cultural heritage in relation to global change across the federal agencies most responsible for addressing that global change is remedial.…”
Section: Department Of Commercementioning
confidence: 99%